2020
DOI: 10.21203/rs.3.rs-25249/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognostic Value of Lymph Node to Primary Tumor Standardized Uptake Value Ratio in Unresectable Esophageal Cancer

Abstract: Background Unresectable esophageal cancer harbors high mortality despite chemoradiotherapy. Better patient selection for more personalized management may result in better treatment outcomes. We presume the ratio of maximum standardized uptake value (SUV) of metastatic lymph nodes to primary tumor (NTR) in 2-deoxy-2-[18F]fluoro-D-glucose positron emission tomography/computed tomography (FDG PET/CT) may provide prognostic information and further stratification of these patients. Methods The patients with non-meta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The pathogenic factors of ovarian tumors are unclear, but the environmental and endocrine effects are the most important among the pathogenic factors of ovarian tumors. Studies to date have confirmed that the LNR has good predictive value for the prognosis of patients with malignant tumors, including ovarian cancers (12)(13)(14)(15)(16)(17)(18)(19)(20). Preoperative chemotherapy has a certain impact on the lymph node status of patients with malignant tumors.…”
Section: Discussionmentioning
confidence: 97%
“…The pathogenic factors of ovarian tumors are unclear, but the environmental and endocrine effects are the most important among the pathogenic factors of ovarian tumors. Studies to date have confirmed that the LNR has good predictive value for the prognosis of patients with malignant tumors, including ovarian cancers (12)(13)(14)(15)(16)(17)(18)(19)(20). Preoperative chemotherapy has a certain impact on the lymph node status of patients with malignant tumors.…”
Section: Discussionmentioning
confidence: 97%
“…In their report, multivariable analysis showed that NTR was an independent prognostic factor for distant metastasis-free survival (hazard ratio 2.20, 95% CI 1.20–4.03, P = 0.011). Similarly, it has been demonstrated that NTR was an independent factor for predicting prognosis in unresectable esophageal cancer [10], endometrioid endometrial carcinoma [11], and invasive ductal breast cancer [33]. Kaira et al [34] found that higher ratio of SUVmax of the metastatic tumor to the primary tumor (M/P ratio) portended lower response to initial chemotherapy and poorer survival (PFS and OS) in stage IIIB and IV NSCLC patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these traditional PET parameters, several recent studies investigated the role of a ratio parameter called the ratio of maximum standardized uptake value (SUV) of metastatic lymph nodes to primary tumor (NTR) [9][10][11][12]. Several studies had found that the patients with relatively high NTR are significantly associated with poor outcomes, suggesting that the NTR has different behaviors between tumors with higher and lower metastatic potential [10,12]. However, few studies investigated the prognostic value of NTR in NSCLC patients treated with concurrent chemo-radiotherapy.…”
Section: Introductionmentioning
confidence: 99%